2015
DOI: 10.3389/fphar.2015.00076
|View full text |Cite
|
Sign up to set email alerts
|

Long term follow up of patients after allogeneic stem cell transplantation and transfusion of HSV-TK transduced T-cells

Abstract: Allogeneic stem cell transplantation (allo-HSCT) is one of the curative treatments for hematologic malignancies, but is hampered by severe complications, such as acute or chronic graft-versus-host-disease (aGvHD; cGvHD) and infections. CD34-selection of stem cells reduces the risk of aGvHD, but also leads to increased infectious complications and relapse. Thus, we studied the safety, efficacy, and feasibility of transfer of gene modified donor T-cells shortly after allo-HSCT in two clinical trials between 2002… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 27 publications
0
11
0
Order By: Relevance
“…Thus, ex vivo T-cell depletion by either CD34 + cell selection or CD3 + /CD19 + cell depletion has not been routinely performed and repletion protocols have been widely studied [e.g., HSV-Tk-transduced T cell transfer, other donor lymphocyte infusion-based protocols (109, 110)]. In vivo T cell reducing or impairing agents include ATG [e.g., ATG-Fresenius; Germany, or thymoglobulin (thymo); Genzyme; USA] or anti-CD52 antibody (alemtuzumab or campath), a particularly powerful reagent for immunosuppression (108, 111).…”
Section: Adaptive Immunitymentioning
confidence: 99%
“…Thus, ex vivo T-cell depletion by either CD34 + cell selection or CD3 + /CD19 + cell depletion has not been routinely performed and repletion protocols have been widely studied [e.g., HSV-Tk-transduced T cell transfer, other donor lymphocyte infusion-based protocols (109, 110)]. In vivo T cell reducing or impairing agents include ATG [e.g., ATG-Fresenius; Germany, or thymoglobulin (thymo); Genzyme; USA] or anti-CD52 antibody (alemtuzumab or campath), a particularly powerful reagent for immunosuppression (108, 111).…”
Section: Adaptive Immunitymentioning
confidence: 99%
“…An alternative method of controlling CAR T cell activity and specificity is to make a universal CAR T cell whose CAR receptor can be docked with an antibody or antibody fragment that gives the cell different specificity (Figure 2c). This approach has been described by multiple groups using a variety of docking interactions, such as avidin-biotin, antibody-small molecule, and antibody-peptide binding pairs (119123). However, these studies also showed the precise orientation of the antigen-binding components of these receptors affects CAR activity.…”
Section: What Is Synthetic Biology?mentioning
confidence: 99%
“…In the initial report, the successfully transduced cells were positively selected using a truncated version of the nerve growth factor receptor that was coexpressed with the viral thymidine kinase (139). In the initial investigation and in subsequent clinical trials using similar HSV-TK systems, patients who received modified donor T cells after allogeneic stem cell transplants and subsequently developed GVHD were successfully treated with ganciclovir (123). However, an anti-HSV-TK immune response has been described in some patients, which in some cases led to immune-mediated elimination of the genetically modified allogeneic T cells.…”
Section: Safety Of Engineered T Cell Therapeuticsmentioning
confidence: 99%
“…In the TK suicide gene/ prodrug system, only alloreactive gene-modified T cells that proliferate actively during GVHD are killed by GCV, whereas resting transduced T cells and untransduced cells are spared. TK gene therapy has proven to be safe, with no documented adverse events related to the gene-transfer procedure, including appearance of replication-competent retroviruses or genotoxic effects of vector integration [61][62][63][64][65][66][67][68][69][70][71].…”
Section: Suicide Gene Therapymentioning
confidence: 99%